2020
DOI: 10.22225/wmj.5.1.1793.8-15
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Chemical, and Biological Water Quality Characteristics of Buyan Lake and Tamblingan Lake

Abstract: Buyan Lake and Tamblingan Lake are known as twin lakes in Bali which serve not only as water sources for agriculture and households, but also as tourist destinations. Infrastructure development and the up-surge of tourism activities potentially increase the contamination of lake water in Bali. The aim of this study was to investigate the quality of water in Buyan Lake and Tamblingan Lake based on physical, chemical, and biological parameters. Five sampling sites (stations) were purposively chosen in ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Some other Coliforms that should be avoided are Salmonella Typhi which triggers typhoid fever (typhoid). When these bacteria enter through the mouth and spread in the body, this can lead to digestive disorder characterized by symptoms such as fever, headache, abdominal pain, and decreased appetite (Sukmawati 2020). Water Quality is a quality characteristic needed for human survival.…”
Section: Biologicalmentioning
confidence: 99%
“…Some other Coliforms that should be avoided are Salmonella Typhi which triggers typhoid fever (typhoid). When these bacteria enter through the mouth and spread in the body, this can lead to digestive disorder characterized by symptoms such as fever, headache, abdominal pain, and decreased appetite (Sukmawati 2020). Water Quality is a quality characteristic needed for human survival.…”
Section: Biologicalmentioning
confidence: 99%
“…Mushtaq (17) analysed the water quality data of Dal Lake, Kashmir in 2005 and 2015 using NSF-WQI method and found that high pollution level and bad quality of water. Sukmawati and Rusni (18) analysed the water quality data of Beratan Lake, Indonesia and found that the water quality of the lake is good and also suggested that NFS-WQI method, is best method to provide overall information. Bouhezila (19) analysed the water quality data of Réghaïa lake, Algeria, using various WQI methods and found that the water quality of lake is poor and unsuitable for irrigation purpose.…”
Section: Introductionmentioning
confidence: 99%